2006
DOI: 10.1007/s00262-006-0240-9
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant properties of listeriolysin O protein in a DNA vaccination strategy

Abstract: The use of infectious agents as vaccine adjuvants has shown utility in both prophylactic and therapeutic vaccinations. Listeria monocytogenes has been used extensively as a vaccine vehicle due to its ability to initiate both CD4(+) and CD8(+) immune responses. Previous work from this laboratory has used transgenic Listeria to deliver vaccine constructs. A chimeric protein composed of tumor antigen and a non-hemolytic variant of the Listeria protein, listeriolysin O (LLO), has demonstrated effective tumor prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…In accordance with the PAMP hypothesis, LLO has been reported to improve antigen presentation in the context of major histocompatibility complex (MHC) class I molecules and to enhance T cell-mediated immune responses when genetically fused to (12)(13)(14), mixed with (15), or conjugated to (16) antigens. The adjuvant properties of LLO have been demonstrated not only in the context of L. monocytogenes (17) but also in various vaccine platforms, such as modified vaccinia virus Ankara (MVA) or plasmid DNA (pDNA), and as a protein carrier for anti-idiotypic immune therapy of non-Hodgkin's lymphoma (12,13,(17)(18)(19)(20), suggesting broad applicability in immunotherapeutic strategies.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In accordance with the PAMP hypothesis, LLO has been reported to improve antigen presentation in the context of major histocompatibility complex (MHC) class I molecules and to enhance T cell-mediated immune responses when genetically fused to (12)(13)(14), mixed with (15), or conjugated to (16) antigens. The adjuvant properties of LLO have been demonstrated not only in the context of L. monocytogenes (17) but also in various vaccine platforms, such as modified vaccinia virus Ankara (MVA) or plasmid DNA (pDNA), and as a protein carrier for anti-idiotypic immune therapy of non-Hodgkin's lymphoma (12,13,(17)(18)(19)(20), suggesting broad applicability in immunotherapeutic strategies.…”
mentioning
confidence: 93%
“…The adjuvant properties of LLO have been demonstrated not only in the context of L. monocytogenes (17) but also in various vaccine platforms, such as modified vaccinia virus Ankara (MVA) or plasmid DNA (pDNA), and as a protein carrier for anti-idiotypic immune therapy of non-Hodgkin's lymphoma (12,13,(17)(18)(19)(20), suggesting broad applicability in immunotherapeutic strategies. Although there are sufficient data supporting LLO as a potent immune activator, how it exerts these effects is unknown.…”
mentioning
confidence: 99%
“…In addition to enhanced proteasomal degradation and presentation on MHC I, we hypothesized that differences in the efficacy of the two vaccines were linked, in part, to the ability of each of the vaccine strains to render otherwise immature professional antigen presenting cells such as dendritic cells (DCs) into effective, mature APCs [31]. In vitro comparisons of Lm-E7, Lm-LLO-E7, and wild-type Listeria monocytogenes revealed enhanced upregulation by Lm-LLO-E7 of MHC II as well as CD40, CD80, CD86, B7-HI, and B7-DC on bone marrow derived DCs.…”
Section: Listeria Monocytogenes As a Vector For Human Tumor Antigensmentioning
confidence: 99%
“…In order to separate the non-specific effects of Lm infection from the adjuvant effect of LLO for these studies, we employed the use of a eukaryotic expression vector to produce a series of DNA vaccines [31]. The DNA vaccines expressed either E7 alone (pcDNA3.1-E7), LLO alone (pcDNA3.1-LLO), LLO fused to E7 (pcDNA3.1-LLOE7), or LLO and E7 expressed as a bicistronic message (pcDNA3.1-LLO-IRES-E7).…”
Section: Listeria Monocytogenes As a Vector For Human Tumor Antigensmentioning
confidence: 99%
“…In fact, Paterson's group showed that LLO can act as an adjuvant for anti-tumor vaccines without being fused to the tumor antigen and can be expressed alone without reducing the vaccine potency. 124 A heterologous prime-boost immunization strategy is currently predominantly utilized to conquer the problem of vectorpointing immune responses in cancer immunotherapy. To date, the heterologous prime-boost regimen is among the most potent strategy used to induce cellular immune responses.…”
Section: Llo-based Immunotoxin/immunoliposome For Killing Tumor Cellsmentioning
confidence: 99%